The Effect of PBL Model and Learning Motivation on the Mathematical Connection Ability of Class VIII MTs Darussalam Batumarta Students - Rosidah, Nur; Hadi, Sopiyan; Noviyanti, Mery (Edumaspul: Jurnal Pendidikan, 2024)
Students in the eighth grade during the second half of the 2022–2023 school year were the focus of this research, which examines how the project-based learning (PBL) model and students' intrinsic motivation to learn affected their capacity to make mathematical connections. There was a quantitative approach to this research. Methods such as observation, interviews, documentation, surveys, and testing are used to gather data. This study used a quasi-experimental design. Because the individuals already existed before to the research, subject selection was not random. Using the total sampling approach, 66 students, representing the whole eighth grade, were selected as the population. Both tests and non-tests are used in the data collecting technique. Research consists of many stages, such as planning, execution, and data processing. Data analysis approaches involve quantitative data analysis and data quality assessment. Based on the results of research and discussion, it is known that 1) there are differences in the mathematical connection ability of students who obtain PBL model learning with students who obtain conventional model learning; 2) there is a difference in the increase in the mathematical connection ability of students who obtain PBL model learning with students who obtain conventional model learning; 3) there are differences in the mathematical connection ability of students who obtain PBL model learning with students who obtain conventional model learning on strong learning motivation; 4) there are differences in the mathematical connection ability of students who obtain PBL model learning with students who obtain conventional model learning on weak learning motivation; 5) there is an interaction between the use of learning methods and student learning motivation on the ability to solve thematic connection problems; and 6) there is a significant influence or interaction between the use of PBL models and the level of learning motivation on mathematical connection ability.